2018
DOI: 10.3390/ijerph15020343
|View full text |Cite
|
Sign up to set email alerts
|

Physical Health Care for People with Severe Mental Illness: the Attitudes, Practices, and Training Needs of Nurses in Three Asian Countries

Abstract: People with severe mental illness (SMI) have considerable unmet physical health needs and an increased risk of early mortality. This cross-sectional survey utilized the Physical Health Attitude Scale (PHASe) to examine the attitudes, practices, and training needs of nurses towards physical health care of people with SMI in three Asian countries (Hong Kong, Japan, Qatar). Cross-country differences were explored and linear regression was used to investigate if nurses’ attitudes and confidence were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 36 publications
4
39
0
5
Order By: Relevance
“…Nurses working in mental health need to be competent to provide physical health care to service users (McCloughen et al, 2015) but their educational preparation can influence their physical health care provision. Professional development to increase all nurses' physical health literacy and skills is important to improve the health disparity experienced by mental health service users (Bressington et al, 2018;Hemingway et al, 2014).…”
Section: Con Clus Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses working in mental health need to be competent to provide physical health care to service users (McCloughen et al, 2015) but their educational preparation can influence their physical health care provision. Professional development to increase all nurses' physical health literacy and skills is important to improve the health disparity experienced by mental health service users (Bressington et al, 2018;Hemingway et al, 2014).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…However, at the clinical level providing physical health care remains a challenge for many nurses working in mental health setting (Ward, Wynaden, & Heslop, ; Wynaden et al., ). Several studies (Bressington et al., ; Ganiah, Al‐Hussami, & Alhadidi, ; Happell, Platania‐Phung, & Scott, ; Robson, Haddad, Gray, & Gournay, ) have been completed to gain an improved understanding of the challenges nurses experience using a quantitative measurement tool developed by Robson and Haddad (), and to evaluate attitudes nurses hold towards physical health promotion activities (Happell & Platania‐Phung, ; Wynaden et al., ). A qualitative study also identified the need for mental health nurses to change their nursing practices to address the unmet physical health care needs of mental health service users (Gray & Brown, ).…”
Section: Introductionmentioning
confidence: 99%
“…With this purpose in mind and considering the wide range of nursing interventions identified in the information systems in Portugal, all the interventions that were not specifically associated with mental health and psychiatry were excluded, including those associated with physical health care. Bearing in mind the relationship between mental and physical health supported by the literature (Blythe & White, ; Bressington et al, ; Robson, Haddad, Gray, & Gournay, ), this could be a limitation, because it may have led to the exclusion of certain important aspects of mental health nursing.…”
Section: Discussionmentioning
confidence: 99%
“…One other published study of MAEs in mental health hospitals conducted a similar comparison, finding that a greater proportion of errors involved non-oral administration routes on two elderly units [18]. Targeted investigation into the causes of this observation could include exploration of variable practices of medication storage (noted to be a causative factor in some types of MAE in psychiatry [9]) and awareness and training of specialist mental health staff in physical health illnesses which has been previously highlighted as an area for development for nurses, for example [33,34].…”
Section: Implications Of Findingsmentioning
confidence: 94%